Economic Development Of Rantau Karya Village Community Air Sugihan District, Ogan Komering Ilir Regency 2011 – 2017 (Contribution Of Materials To The Course Economic History Of History Education Of Sriwijaya University) - Mindarto Mindarto; Yunani Yunani; Alian Alian (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2018)
This study entitled